Accounting for False Objectivity - Palliam, Ralph (2011)
Corporate scandals and misleading financial statement reporting have raised serious concerns surrounding standards in all forms of governance and have given one an opportunity to discredit capitalism as an economic system. An element of distrust pervades every line of worthwhile endeavor. Stockholders, bondholders and other stakeholders who include employees, suppliers and consumers are continually pre-occupied in determining the worthiness of financial reports. Elements of distrust have come to pervade modern commerce and corporations and economies have yet to recover from the stigma of deceit. The credibility of accounting standards together with its professional ethics is being consistently questioned. The collapse of major corporations and economies reveals the extent to which the accounting profession was actively involved in manipulating financial results and financial positions within the confines of generally accepted accounting practices and ethical standards established by professional boards. Performance and progress statements that do not accurately capture the reality of an entity affect numerous stakeholders. Financial institutions in particular get to misallocate scarce financial resources and such conduct has devastating consequences. Moreover, when long serving and committed company employees are duped into providing their skills to entities that have a limited future, the moral fiber of corporations and society comes in question. Whilst objectivity is the aim of those who manage a corporation, there are some who stand to gain from cooperating with management to falsify the accounting system to produce a misleading, distorted, and downright fictional portrayal of a business’s health and prospects.